Contrast‐enhanced ultrasound repeatability for the measurement of skeletal muscle microvascular blood flow. Issue 4 (4th February 2023) - Jones, Eleanor J.; Atherton, Philip J.; Piasecki, Mathew; Phillips, Bethan E.
Abstract : New Findings: What is the central question of this study? Contrast‐enhanced ultrasound (CEUS) can be used to directly assess skeletal muscle perfusion but its day‐to‐day repeatability over time has not yet been validated: is CEUS a repeatable method for the measurement of skeletal muscle microvascular blood flow (MBF) at rest and in response to exercise, across independent assessment sessions? What is the main finding and its importance? A strong agreement between CEUS MBF measures across sessions suggests it is a repeatable method for assessing skeletal muscle perfusion over time. This validation provides confidence for incorporating these measures into longitudinal studies such as a chronic intervention or disease progression to gain further knowledge of skeletal muscle microvascular function. Abstract: Contrast‐enhanced ultrasound (CEUS) can be used to directly assess skeletal muscle perfusion. However, its repeatability over time has not yet been validated and therefore its use in longitudinal measures (i.e., exploring the impact of a chronic intervention or disease progression) is limited. This study aimed to determine the repeatability of CEUS for the measurement of skeletal muscle microvascular blood flow (MBF) at baseline and in response to exercise, across independent assessment sessions. Ten healthy volunteers (five female; 30 ± 6 years) had CEUS of the right vastus lateralis recorded in two separate sessions, 14 days apart. Measurements were taken at baseline, during an isometric leg extension and during recovery. Acoustic intensity data from a region of interest were plotted as a replenishment curve to obtain blood volume ( A ) and flow velocity (β) values from a one‐phase association non‐linear regression of mean tissue echogenicity. Linear regression and Bland–Altman analyses of A and β values were performed, with significance assumed as P < 0.05. Strong positive correlations were observed across sessions for all A and β values (both P < 0.0001). Bland–Altman analysis showed a bias (SD) of −0.013 ± 1.24 for A and −0.014 ± 0.31 for β. A bias of 0.201 ± 0.770 at baseline, 0.527 ± 1.29 during contraction and −0.203 ± 1.29 at recovery was observed for A, and −0.0328 ± 0.0853 (baseline), −0.0446 ± 0.206 (contraction) and 0.0382 ± 0.233 (recovery) for β. A strong agreement between CEUS MBF measures across independent sessions suggests it to be a repeatable method for assessing skeletal muscle perfusion over time, and therefore facilitates wider use in longitudinal studies.